The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.11604/pamj.2016.24.170.4782
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in Moroccan pregnant women and newborns: reports of 102 cases

Abstract: IntroductionVitamin D insufficiency to pregnant women has been associated with a number of adverse consequences, and has been recognized as a public health concern. The aim of this study was to evaluate vitamin D status of Morrocan pregnant women and their newborns. Our study is being the first of its kind in Morocco, as it supports the program of systematic supplementation of pregnant women in the third quarter. Its results have established a new program for the fight against the deficit of various nutrients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…As for data from other countries, Rodriguez et al and Eggemoen et al found no connection between neonatal anthropometric parameters and maternal vitamin D levels, even despite the fact that vitamin D deficiency (<20 ng/ml) was detected in 19.7% and 51% of the women, respectively ( 18 , 35 ). Loudyi et al reported no association between maternal vitamin D status and neonatal weight at birth among the investigated women (vitamin D concentration ≤20 ng/ml in 90% of the cases) ( 36 ). Shakiba and Iranmanesh and Josefson et al found no relationship between cord vitamin D concentration and neonatal weight and length ( 25 , 31 ), while Dalgård et al reported the same lack of relationship for neonatal weight and head circumference ( 37 ).…”
Section: Discussionmentioning
confidence: 98%
“…As for data from other countries, Rodriguez et al and Eggemoen et al found no connection between neonatal anthropometric parameters and maternal vitamin D levels, even despite the fact that vitamin D deficiency (<20 ng/ml) was detected in 19.7% and 51% of the women, respectively ( 18 , 35 ). Loudyi et al reported no association between maternal vitamin D status and neonatal weight at birth among the investigated women (vitamin D concentration ≤20 ng/ml in 90% of the cases) ( 36 ). Shakiba and Iranmanesh and Josefson et al found no relationship between cord vitamin D concentration and neonatal weight and length ( 25 , 31 ), while Dalgård et al reported the same lack of relationship for neonatal weight and head circumference ( 37 ).…”
Section: Discussionmentioning
confidence: 98%
“…Maternal nutrition prior to and during pregnancy play a central role in determining the long-term health and nutritional effect of both the mother and her growing fetus [9, 21]. Maternal undernutrition is highly prevalent in low and middle-income countries [7, 9, 10] and Ethiopia as one of these countries has been significantly affected by the burden of undernutrition. We conducted a cross-sectional study to identify the burden and associated factors of undernutrition among pregnant mothers residing in an urban setting.…”
Section: Discussionmentioning
confidence: 99%
“…Ethiopia is one of the countries with a high burden of maternal and child undernutrition. Though, maternal undernutrition has declined over the past 16 years, from 30% in 2000 to 22% in 2016, Ethiopia is still among countries with a high burden of maternal malnutrition [7]. Specifically, two institution based cross-sectional studies conducted in Amhara region reported a prevalence rate of undernutrition ranging from 16% to 29.8% that also showed a significant geographic variation [3, 8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few published data on vitamin D status during pregnancy in African countries and there is a high rate (20.0%) of obesity among pregnant Sudanese women . Moreover maternal obesity is associated with maternal and perinatal adverse effects .…”
Section: Introductionmentioning
confidence: 99%